Analysis of Factors Affecting the Profitability of Village Credit Institutions in Banjarangkan Klungkung - Putu Kepramareni; Sagung Oka Pradnyawati; I Komang Tri Mahendra (AIBPM Publisher, 2022)
This study examines the factors affecting the ability of village credit institutions to obtain profits with profitability as a measuring tool. Credit turnover rate, debt management effectiveness, number of credit customers, capital and operating expenses were used as research variables. The determination method was a non-probability sampling method, especially purposive sampling. Data was collected by means of non-participant observation. The data were analyzed by multiple linear regression analysis. The test results show that credit turnover, debt management effectiveness, and capital provide a positive direction on profitability. The number of credit customers has no effect on profitability and the negative effect on profitability is shown by the BOPO variable. This study underlines several factors to support LPD earnings. Keywords: BOPO, Credit Turnover Rate, Effectiveness of Debt Management, LPD Capital, Number of Credit Customers, Profitability, Village Credit Institution (LPD)